2020
DOI: 10.1124/dmd.120.000171
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Characterization of Ertugliflozin Metabolism by UDP-Glucuronosyltransferase and Cytochrome P450 Enzymes

Abstract: Ertugliflozin is primarily cleared through UDP-glucurosyltransferase (UGT)-mediated metabolism (86%) with minor oxidative clearance (12%). In vitro phenotyping involved enzyme kinetic characterization of UGTs or cytochrome P450 (CYP) enzymes catalyzing formation of the major 3-O-β-glucuronide (M5c) and minor 2-O-β-glucuronide (M5a), monohydroxy-ertugliflozin (M1 and M3), and des-ethyl ertugliflozin (M2) metabolites in human liver microsomes (HLM). Fractional clearance (fCL) from HLM intrinsic clearance (CLint)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 46 publications
1
21
0
Order By: Relevance
“…As selective inhibitors of UGT2B4 and UGT2B7 are not available, the minor UGT enzymes are reported as UGT2B4/2B7 (19%). 12,17,18 Because MFA inhibits UGT1A9 and UGT2B7, and not UGT2B4, the minor UGT responsible for metabolism of ertugliflozin was assigned to UGT2B7 in the PBPK model. This assignment provides a conservative assessment of the DDI following co-administration of ertugliflozin with the UGT1A9/2B7 inhibitor MFA.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…As selective inhibitors of UGT2B4 and UGT2B7 are not available, the minor UGT enzymes are reported as UGT2B4/2B7 (19%). 12,17,18 Because MFA inhibits UGT1A9 and UGT2B7, and not UGT2B4, the minor UGT responsible for metabolism of ertugliflozin was assigned to UGT2B7 in the PBPK model. This assignment provides a conservative assessment of the DDI following co-administration of ertugliflozin with the UGT1A9/2B7 inhibitor MFA.…”
Section: Discussionmentioning
confidence: 99%
“…The minor UGT enzymes were assigned based on studies with the UGT inhibitor 16β‐phenyllongifolol, which was recently shown to be a nonselective inhibitor of both UGT2B4 and UGT2B7. As selective inhibitors of UGT2B4 and UGT2B7 are not available, the minor UGT enzymes are reported as UGT2B4/2B7 (19%) 12,17,18 . Because MFA inhibits UGT1A9 and UGT2B7, and not UGT2B4, the minor UGT responsible for metabolism of ertugliflozin was assigned to UGT2B7 in the PBPK model.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations